FTIR Analysis of Pesticide Active Ingredients into Seasonal Vegetables: Ensuring Food Safety and Raising Awareness - Md. Mejbah Uddin Mithu; Sadia Akter Shormela (Journal of Global Innovations in Agricultural Sciences)
Bangladesh's agriculture sector heavily relies on the use of pesticides for pest control and production. However, improper use and unsafe handling practices can lead to the bio-accumulation of pesticide active ingredients in vegetables, causing high farmer exposure and adverse health effects. This study aimed to detect the presence of pesticide active ingredients in raw vegetables using Infrared Spectroscopy (IR). The study involved four fruit vegetables (Eggplants, Tomatoes, Bitter gourd, Green-bean) and 11 different pesticides used by farmers. The results showed that the most widely applied pesticides were moderately toxic WHO class II pesticides. Organophosphate, Neonicotinoid, and fungicide were found in fruits vegetables (Green bean, bitter gourd & eggplant). Food contamination is a serious concern for developing countries, including Bangladesh. Improper pesticide application can lead to a buildup of agrochemical active ingredients on plants' edible portions, potentially absorbing into the food chain. Programs like farmer’s field school, integrated pest management, and the department of agricultural extension's awareness program can help enhance knowledge about effective pesticide usage and prevent health issues related to personal health and safety. It is crucial to limit and avoid misuse and overdose of pesticides in vegetables to prevent the distribution of pesticide molecules and prevent acute and chronic health complications.